IDENTITY NEGOTIATION: AMERICAN AND INDONESIAN CULTURAL HYBRIDITY IN THE HOSPITALITY INDUSTRY - Nawangsih Edynna Putri; Arie Restama; Nathaniel Nicolas Ryan (International Journal of Social Science, 2026)
Globalization allows the rapid spread of American popular culture, including the Halloween celebration, to various countries, including Indonesia. Halloween is no longer represented as an authentic American culture as it adapts to Indonesian local culture. This research aims to reveal the cultural hybridity representations in Javanese traditional Halloween events organized by hotels in Indonesia and analyze the cultural hybridity formulations. This research employed a qualitative method, using Homi K. Bhabha’s theory of cultural hybridity. Data were collected through a literature study and documentation, such as footage of Halloween celebrations at hotels in Indonesia. The findings reveal that Halloween events at hotels in Indonesia embody three main concepts of Bhabha’s cultural hybridity, encompassing Third Space, Mimicry, and Ambivalence. Third Space is represented in the formulation of a new cultural product, a Javanese-themed Halloween, combining Indonesian and American cultural narrations, symbols, and aesthetics. Mimicry is reflected in partial imitation of American Halloween and cultural adaptations, presenting Javanese mystics as the main identity. Ambivalence is portrayed in the hotel’s strategy to adopt global trends and how the hotel industry maintains the local cultural identity as the differentiator. Halloween events organized by hotels in Indonesia are a practical cultural production, highlighting the ability of the hospitality industry to negotiate global and local cultures in forming a contextual hybrid cultural identity and to strengthen destination difference in the hospitality industry